Data for "DNA fluctuations reveal the size and dynamics of topological domains" - Lipfert, Jan (Utrecht University, 2022)
These are the data for the manuscript
"DNA fluctuations reveal the size and dynamics of topological domains"
Willem Vanderlinden, Enrico Skoruppa, Pauline Kolbeck, Enrico Carlon, and Jan Lipfert
PNAS Nexus (2022)

Please cite this reference when using or referring to these data.

The data sets contain experimental data and data from Monte Carlo simulations
- The data are organized by which figure in the main text they are presented in.

- The experimental data were generated by single-molecule magnetic tweezers measurements of DNA under defined forces and torques. The consist both of raw extension vs. time traces (both for bare DNA and in the presence of enzymes) and of analyzed data based on these extension time traces.

For Figure 1 and 4 we provide magnetic tweezers traces as text files with 6 columns, in the following format:
Column 1: Time in ms
Column 2: X position in µm
Column 3: Y position in µm
Column 4: Z position in µm
Column 5: Magnet Height (above the flow cell) in mm
Column 6: Magnet Rotation in turns

- The simulation data were generated by Monte Carlo simulations of DNA treated as an elastic rod.
Keywords: Natural Sciences - Physical sciences (1.3); DNA; Magnetic tweezers; Monte Carlo Simulations; Supercoiling; Fluctuations